Finding order in measuring disorders: Measurement Uncertainty of Thyroid Function Tests at a tertiary care hospital in Eastern India - Asis Bhattacharya,; Kasturi Mukherjee,; Arkajit Dasgupta,; Debi Mallick,; Mousumi Mukhopadhyay, (Asian Journal of Medical Sciences, 2025)
Background: Quantitative estimation of analytes in the laboratory is the mainstay of disease diagnosis. However, the true value of the analyte cannot be measured. Hence, the clinical validity of a test requires a concurrent statement of uncertainty. The International Organization for Standardization further mandates that measurement uncertainty (MU) for all parameters be included in medical reports for laboratory accreditation. Yet, studies regarding the uncertainty of measurement across instruments and parameters remain elusive in India. Thyroid disorders constitute a global health menace but can be efficiently managed if diagnosed early via reliable immunoassays. However, such immunoassays may be altered by different variables, necessitating the addition of the uncertainty statement for proper evaluation of the hormonal status. Aims and Objectives: Present study aimed to determine the uncertainty of measurement in estimating free thyroxine and thyroid-stimulating hormone (TSH) levels in the immunoassay laboratory of a tertiary care hospital in Eastern India. Materials and Methods: In this hospital-based descriptive study, MU was calculated using internal quality control and external quality assurance data, adapting a top-down approach as per the Guide to the expression of uncertainty in measurement documents. Results: Using three levels of immunoassay controls, MU for free thyroxine was 0.08, 0.08, and 0.21, while it was 0.03, 0.21 and 0.53 for TSH. Conclusion: Incorporation of uncertainty data alongside individual patient reports can help physicians gain more comprehensive information regarding diseases. The present study can act as a stepping stone for further research in India to facilitate greater quality of patient care laboratory services.